The Relationship between Banking Competition and Stability in Developing Countries: The Case of Libya - Troug, Haytem Ahmed; Sbia, Rashid (International Journal of Economics and Financial Issues, 2015)
In our paper, we examined the relationship between non-performing loans, as a measure of stability, and concentration, as a measure of competition, in the Libyan banking sector. We used aggregate quarterly data for the 15 commercial banks in the country during the period 2002-2013. A broad set of tests were conducted to measure the relationship between the two variables, and alternative robustness tests were conducted to verify our core finding that less competition in the banking sector leads to a more resilient banking sector. Thus, our results offer empirical support against the “competition–stability” theory and conform the “competition–fragility” literature. We conclude by recommending the need to inspect in more detail (on a bank by bank level) the relationship between competition and fragility in developing countries in general and in Libya in particular. Keywords: Banking Competition; Financial Stability; Oil exporting countries; MENA; Libya. JEL Classifications: C50; C58; G21; G28.